Perdagangan Bebas Produk Farmasi dan Alat Kesehatan serta Kesiapan Memenuhi Persyaratan Cetak Biru Masyarakat Ekonomi ASEAN - Prayitno, Lukman; Herman, Max Joseph (Jurnal Kefarmasian Indonesia, 2020)
The implementation of the ASEAN Economic Community (AEC) as an Indonesian Government’s strategic step has an impact on economic globalization. The study on pharmaceutical products and medical devices free trade was done using qualitative and quantitative methods. The data were collected from a round table discussion about "Free Trade in Health Goods and Services in ASEAN" which involved the Ministry of Health (MoH), Ministry of Trade (MoT), and National Agency for Drug and Food Control (NADFC). The discussion aimed to obtain information on the readiness to meet the AEC blueprint. Secondary data on export and import of pharmaceutical products and medical devices were obtained from the MoT. The results of the study show that between 2013 and 2017 there were 70-72 product items exported to 9 ASEAN countries with a value much greater than the import. The tariff measure (TM) requirements included the Most Favored Nation (MFN) assessment and regulation of the trade remedy procedure by MoH and MoT. The implementation of ASEAN Common Technical Dossier (ACTD) and Good Manufacturing Practice inspection agreements, Bioequivalence reporting agreements, agreements related to traditional medicines and health supplement have been done by NADFC and industry. The simplification of Certificate of Origin, operation certification procedures and realization of ASEAN self-certification have to be specified. MoH must coordinate with NADFC and MoT in deciding and implementing regulations